The given expression can be simplified by combining like terms:
z^2 - 4z - 3z + 2z^2 + z - 12
= 3z^2 - 6z - 12
= 3(z^2 - 2z - 4)
Therefore, the quotient in simplest form is 3(z^2 - 2z - 4). There are no restrictions on the variable.
What is the quotient in simplest form? State any restrictions on the variable.
z2-4z-3z+2z2+z-12
2 answers
since you ask about a quotient, I expected to see some division. I'll go with
(z^2-4z-3) / (2z^2+z-12) = 1/2 Rem -9/2 z + 9
I suspect further typos.
(z^2-4z-3) / (2z^2+z-12) = 1/2 Rem -9/2 z + 9
I suspect further typos.